Hubungan Keikutsertaan Prolanis Terhadap Kepatuhan Minum Obat dan Kualitas Hidup Pasien Faskes Pertama di Kota Kendari - Restu Nur Hasanah Haris; Wa Ode Masrida; Muhamad Ramadhan Salam; Misdayanti Misdayanti; Hesti Trisnianti Burhan (CV. Global Cendekia Inti, 2026)
This study examines the relationship between participation in the Chronic Disease Management Program (PROLANIS) and medication adherence, as well as the quality of life among patients at first-level health facilities in Kendari City. PROLANIS is an integrated health service program involving BPJS, health facilities, and patients. Medication adherence is an important factor influencing therapy success and the quality of life. This non-experimental cross-sectional study involved 480 active PROLANIS patients with hypertension and diabetes mellitus, receiving drug therapy. The research took place at the Kendari City Community Health Center from July to September 2024, using purposive sampling. Medication adherence was measured with the MARS-5 instrument, and quality of life was assessed with the SF-6D. Data analysis involved coding, scoring, and bivariate chi-square tests. Non-adherence was defined by a MARS-5 score <25, while adherence was represented by a score of 25 (maximum). A quality of life utility value of 0.00-0.78 indicated low quality, while 0.79-1.00 indicated high quality. The findings revealed that both PROLANIS and non-PROLANIS patients exhibited non-adherence (MARS-5 score <25) but reported high quality of life. Chi-square tests showed a significant relationship between PROLANIS participation and medication adherence (p-value 0.036) as well as quality of life (p-value 0.001).